(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Pregnant women who experience chronic energy deficiency will give birth to babies with low birth weight (LBW) which has an impact on the incidence of stunting (February 2023: 21.7%). Measurement data from February 2023 shows that 414 LBW babies were born, of which 38 children experienced stunting and 12 children did not experience stunting. The research aims to examine the actions of families of toddlers whose children have a history of LBW but are not stunted in Mokdale Village, Lobalain subdistrict, Rote Ndao district, Indonesia. The results of the analysis found that the coping mechanism factors used by mothers of LBW children who were not stunted included: 1). Factors: Mothers of toddlers in the late adult age category (36-45 years) who are able to make decisions regarding parenting patterns and have a stable emotional condition which has a positive influence on parenting patterns; 2). Factor allocation of caregiving time for mothers of toddlers is more than eight hours per day; 3). Behavioral factors (knowledge, attitudes and actions) related to stunting, causes and impacts; 4). Factors: family food consumption patterns have better quality and quantity (>7 types of food consumed per day) and do not have the habit of abstaining from food; 5). Factors including the availability of clean water and the family adopting a clean and healthy lifestyle, including having and using a healthy toilet; 6). Factors do not have a history of infectious diseases; 7). Factors: history of getting enough exclusive breast milk for up to six months; 8). Factors: history of regular and complete immunization; 9). Factor in the number of posyandu visits 8-12 times a year; and 10). Factors of toddlers’ families’ access to specific nutritional intervention programs such as programs for underweight toddlers who receive PMT; program for toddlers who receive Vitamin A and toddlers who suffer from diarrhea who receive Zinc Supplements in preventing stunting.